Shigellosis in Southeast Asia: A systematic review and meta-analysis. Issue 52 (March 2023) - Muzembo, Basilua Andre; Kitahara, Kei; Mitra, Debmalya; Ohno, Ayumu; Khatiwada, Januka; Dutta, Shanta; Miyoshi, Shin-Ichi
Abstract: Background: Southeast Asia is attractive for tourism. Unfortunately, travelers to this region are at risk of becoming infected with Shigella . We conducted a meta-analysis to provide updates on Shigella prevalence in Southeast Asia, along with their serogroups and serotypes. Methods: We conducted a systematic search using PubMed, EMBASE, and Web of Science for peer-reviewed studies from 2000 to November 2022. We selected studies that detected Shigella in stools by culture or polymerase chain reaction (PCR). Two reviewers extracted the data using a standardized form and performed quality assessments using the Joanna Briggs Institute checklist. The random effects model was used to estimate the pooled prevalence of Shigella . Results: During our search, we identified 4376 studies. 29 studies (from six Southeast Asian countries) were included in the systematic review, 21 each in the meta-analysis of the prevalence of Shigella (Sample size: 109545) and the prevalence of Shigella serogroups. The pooled prevalence of Shigella was 4% (95% CI: 4–5%) among diarrhea cases. Shigella sonnei was the most abundant serogroup in Thailand (74%) and Vietnam (57%), whereas Shigella flexneri was dominant in Indonesia (72%) and Cambodia (71%). Shigella dysenteriae and Shigella boydii were uncommon (pooled prevalence of 1% each). The pooled prevalence of Shigella was 5% (95% CI: 4–6%) in children aged <5 years. The pooled prevalence showed a decreasing trend comparing data collected between 2000–2013 (5%; 95% CI: 4–6%) and between 2014–2022 (3%; 95% CI: 2–4%). Shigella prevalence was 6% in studies that included participants with mixed pathogens versus 3% in those without. Shigella flexneri serotype 2a was the most frequently isolated (33%), followed by 3a (21%), 1b (10%), 2b (3%), and 6 (3%). Conclusions: This study provides compelling evidence for the development of effective Shigella vaccines for residents of endemic regions and travellers to these areas.